Kebangkitan Tarekat Kota - Ahmad Amir Aziz (Islamica: Jurnal Studi Keislaman, 2013)
This article tries to analyze the revival of mystical order (tarekat) in urban areas. Experiences reveal that the development of mystical orders in the Muslim world is not free from criticism, either from the insiders or the outsiders. However, mystical orders still exist, and this fact is characterized by the development of different mystical groups in various cities. Political, social and economic factors influence the fluctuation of mystical orders. This article argues that in a number of countries and in Indonesia, the mystical orders have contributed significantly to the socio-religious life of Muslims. The mystical orders become stronger as they are supported by the involvement of middle class group, media publication, and internal strength embedded in the very tradition of mystical orders. The influx of middle class Muslims to the networks of tarekat brings the fresh wind of change since their engagement provides the internal dynamic of tarekat which encounters external influences on the one hand, and the continuing drive to develop on the other.